Using Medicare claims in identifying Alzheimer's disease and related dementias. Issue 3 (8th October 2020) - Jain, Siddharth; Rosenbaum, Paul R.; Reiter, Joseph G.; Hoffman, Geoffrey; Small, Dylan S.; Ha, Jinkyung; Hill, Alexander S.; Wolk, David A.; Gaulton, Timothy; Neuman, Mark D.; Eckenhoff, Roderic G.; Fleisher, Lee A.; et al.
Abstract: Introduction: This study develops a measure of Alzheimer's disease and related dementias (ADRD) using Medicare claims. Methods: Validation resembles the approach of the American Psychological Association, including (1) content validity, (2) construct validity, and (3) predictive validity. Results: We found that four items—a Medicare claim recording ADRD 1 year ago, 2 years ago, 3 years ago, and a total stay of 6 months in a nursing home—exhibit a pattern of association consistent with a single underlying ADRD construct, and presence of any two of these four items predict a direct measure of cognitive function and also future claims for ADRD. Discussion: Our four items are internally consistent with the measurement of a single quantity. The presence of any two items do a better job than a single claim when predicting both a direct measure of cognitive function and future ADRD claims.